Features of competition activity in cyclic sport - Плетенецька [Anna Pletenetska] Анна В’ячеславівна (Slobozhanskyi Herald of Science and Sport, 2013)
The analysis of the competitive activity in cyclic sports, such as skiing, cycling, skating, rowing and kayaking and canoeing, swimming, etc., and identified its specificity. The number of starts made by athletes in competitions of various kinds, varies considerably. The components of competitive activity to some extent reflect the parameters of competitive exercises that affect the technical result. Depending on the sport – the structure of competitive activity on one and the same distance is also different. Analysis of the parameters competitive practices reveal wide variation limits the density of competition (depending on the members hip athletes to «sprint» or «long distance» will vary from weeks to months).